Resources for Social Studies: Info-Graphics Illustrations and Jigsaw Effects on Students' Achievement - Shittu Lukman Olayinka; Telfim Nandoo Nandap (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
The Pedagogical shift to learner-centered instructions entails that teachers need to have pre-requisite skills which will enable them to navigate the teaching and learning process efficiently by enabling them to serve as facilitators of curriculum content in Social Studies. This study examined Resources for Social Studies: info graphics illustrations and their effects on students' achievement. The research design for this study was quasi-experimental. The population of the students consisted of all Social Studies school pupils within Jos-South Local Government Area of Plateau State through random sampling technique 34 (n = 17) students were sampled for the study within the experimental and control groups, Data was collected using the instrument titled “Social Studies Students Achievement Test” (SSSAT) that was content and faced validated to determine its internal consistency while for reliability the test- and retest using alpha conbrach 0.66 and 0.70 was attained respectively. The treatment group was taught using info graphics and Jigsaw stimulated games whereas the control class group was taught using the conventional teaching methods. The research null hypotheses were tested using parametric t-test statistics at the confidence level of 0.05%. The findings of the study showed that there is a significant difference between the experimental and control group with the Tstat 3.30 >Tcrit 2.05 indicating a strong significant difference between the sampled groups, there is no significant difference in the post-test mean scores of male and female students in the experimental group with the Tstat 1.53 < Tcrit 2.14 indicating poor significant difference, there is no significant difference between the mean scores of studies who identified as visual learners and those who are not with the Tstat 0.29 < Tcrit 2.44 indicating a low significant difference between the sampled groups. The study recommended that; specialize in digital content creation by teachers, school administrators encouragement for improvisation of instructional resources, autonomy for teaching in selecting resource materials, considerable budgetary allocation to schools by Federal Government to equip their resource rooms.